Effect of the board game as educational technology on schoolchildren's knowledge on breastfeeding - Fernanda Demutti Pimpão Martins; Luciana Pedrosa Leal; Francisca Márcia Pereira Linhares; Alessandro Henrique da Silva Santos; Gerlaine de Oliveira Leite; Cleide Maria Pontes (Universidade de São Paulo, 2018)
ABSTRACT Objective: to evaluate the effect of the board game as an educational technology on schoolchildren's knowledge on breastfeeding. Method: cluster-randomized clinical trial, held in nine schools, with 99 children in the third grade of elementary school (control group = 51 and intervention group = 48). The pretest was conducted in both groups; intervention consisted in the application of the educational technology immediately after pretest to the intervention group; and the post-test was applied on the 7th and 30th days to both groups. For the analysis of children's knowledge on breastfeeding, we considered the pre- and post-test score means, using the Mann-Whitney test - for comparing the means between groups - and the Wilcoxon test - within the same group. Results: there was no statistically significant difference between the groups in the pretest. In the follow-up, when comparing the groups, there were higher means in the intervention group, on the 7th (19.68 ±1.788) and on the 30th (20.16±1.260) days, with statistically significant difference. Within the intervention group, there was significant increase of the means in the pretest (15.89±3.082) for the 30th day (20.16±1.260). Conclusion: such educational intervention has significantly contributed to the increase in scores of children's knowledge on breastfeeding for the intervention group. UTN: U1111-1184-7386.